The round goby genome provides insights into mechanisms that may facilitate biological invasions - Adrian-Kalchhauser, Irene; Blomberg, Anders; Larsson, Tomas; Musilova, Zuzana; Peart, Claire R; Pippel, Martin; Solbakken, Monica Hongroe; Suurväli, Jaanus; Walser, Jean-Claude; Wilson, Joanna Yvonne; Alm Rosenblad, Magnus; Burguera, Demian; et al. (BMC biology, 2020)
BACKGROUND: The invasive benthic round goby (Neogobius melanostomus) is the most successful temperate invasive fish and has spread in aquatic ecosystems on both sides of the Atlantic. Invasive species constitute powerful in situ experimental systems to study fast adaptation and directional selection on short ecological timescales and present promising case studies to understand factors involved the impressive ability of some species to colonize novel environments. We seize the unique opportunity presented by the round goby invasion to study genomic substrates potentially involved in colonization success. RESULTS: We report a highly contiguous long-read-based genome and analyze gene families that we hypothesize to relate to the ability of these fish to deal with novel environments. The analyses provide novel insights from the large evolutionary scale to the small species-specific scale. We describe expansions in specific cytochrome P450 enzymes, a remarkably diverse innate immune system, an ancient duplication in red light vision accompanied by red skin fluorescence, evolutionary patterns of epigenetic regulators, and the presence of osmoregulatory genes that may have contributed to the round goby's capacity to invade cold and salty waters. A recurring theme across all analyzed gene families is gene expansions. CONCLUSIONS: The expanded innate immune system of round goby may potentially contribute to its ability to colonize novel areas. Since other gene families also feature copy number expansions in the round goby, and since other Gobiidae also feature fascinating environmental adaptations and are excellent colonizers, further long-read genome approaches across the goby family may reveal whether gene copy number expansions are more generally related to the ability to conquer new habitats in Gobiidae or in fish.
Keywords: zvláštnosti životní historie; Fish; Male; PacBio; Olfaction; Adaptation; Epigenetics; Detoxification; mužské pohlaví; Genomics; Vision; Gene duplication; ryby; Innate immunity; Invasive species; Fishes; zavlečené druhy; genom; Animals; ženské pohlaví; zvířata; Introduced Species; Neogobius melanostomus; Osmoregulation; Evolution; Genome; Female; Life History Traits